Análisis de los instrumentos comunicacionales, de posicionamiento y gestión de marca del GAD de Babahoyo - Lema Quinatoa, Nancy Rocio (2020)
The present work presents the analysis of the communicational instruments of brand positioning and management in the Municipal Decentralized Autonomous Government (GAD) of the Babahoyo canton. Being the place to analyze the types of tools used inside and outside the communication department in brand positioning and management. In other words, the analysis allows us to verify the management of the communication instruments and the corporate image of the institution as a strategic management that generates trust in the public. The communication strategy in the Municipal Decentralized Autonomous Government of the Babahoyo canton is displayed efficiently in the administration, with respect to the visual image that they project to their spectators is good. The communication elements managed in the positioning of Babahoyo's GAD brand to promote its brand and inform with truthfulness, accuracy in real time the administrative management and its daily activities are social networks such as; Facebook, Twitter, Instagram and radio as well as; Institutional stationers, Vests, Credentials, Stamps, Fences, external ethical signal parking among others. These media have a greater impact on citizens to be informed of the institutional management carried out by the municipality. It has usually become a necessary element that impacts the growth of identity and its permanence in the company are those that distinguish it from the rest of the competitors, whose objective is to make the audience recognize and be in contact with the brand.